Treating post-traumatic uveitis by intravitreal injection of 0.7 mg dexamethasone implant (a clinical case) - I. E. Ioshin; A. S. Gavrilyuk; A. V. Artamonova (Российский офтальмологический журнал, 2018)
Purpose: to assess the first results of intravitreal injection of an implant of dexamethasone 0.7mg for the treatment of post-traumatic uveitis and prevention of post-traumatic eyeball subatrophy. Material and Methods: patient А., 18 years old, was admitted to the hospital with the following diagnosis: a penetrating wound of the right eyeball, post-traumatic corneal scar, post-traumatic iridocyclitis, a posttraumatic swelling cataract, hemophthalmus, local peripheral retinal detachment. The left eye was undamaged. The right eye was given two intravitreal injections, with an interval of 4 months. Results. The follow-up of the patient showed an improvement after the first intravitreal injection of the implant manifested in reduced inflammatory response of the eye, IOP increased from 8 to 11 mm Hg, elongation of the anterioposterior axis of the eyeball from 16.02 mm to 21.63 mm, practically complete hemophthalmus resorption, a significant reduction of retinal edema. After the second intravitreal injection of the implant the positive changes developed: the visual acuity increased from 0.02 to 0.04, IOP increased from 11 to 14 mm Hg, the anterioposterior axis of the eyeball elongated from 21.63 mm to 21.67 mm, hemophthalmus resorbed completely and the retinal edema reduced. Conclusion. The clinical case demonstrates the effect of intravitreally injected implant of dexamethasone 0.7 mg in arresting the inflammatory process // Russian Ophthalmological Journal, 2016; 3: 85-90. doi: 10.21516/2072-0076-2016-9-3-85-90.